FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA MAHASISWI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS HALU OLEO TAHUN 2022 - Aulia Ghibrani Haidir; Jafriati Jafriati; Irma Yunawati (FKM Universitas Halu Oleo, 2022)
The global prevalence of anemia, since 2000 in the WUS group, has stagnated compared to pregnant women, which has slightly decreased. The Strategic Plan of the Ministry of Health of the Republic of Indonesia for 2015-2019 targets the coverage of giving iron tablets to remittances in stages from 10% (2015) to 30% (2019). The causes of anemia that attack female students as WUS category are divided into two, namely direct causes and indirect causes. The high prevalence of anemia among female students if not handled properly will have a bad impact when they are married because it can cause maternal death, premature birth, and babies with low birth weight. This study aims to determine the relationship of disease history, physical activity, dietary behavior and sleep quality with the incidence of anemia in students of the Faculty of Public Health. This type of research is analytic using a cross sectional approach. The number of samples was 98 people who were selected using proportionate stratified random sampling. The analysis used is bivariate analysis using Chi Square test. The results showed that there were 52 who were anemic and 46 were not anemic. In addition, there is a relationship between physical activity (p value = 0.025), and sleep quality (p value = 0.001) with the incidence of anemia, but there is no relationship between disease history (p value = 0.811) and dietary behavior (p value = 0.721). with anemia. The results of the study concluded that there was a relationship between physical activity and sleep quality with the incidence of anemia, while there was no relationship between disease history and dietary behavior with the incidence of anemia..